URGENSI PENDIDIKAN WIRAUSAHA (ENTERPRENEUR) BAGI MAHASISWA - Febriyanto (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2013)
Increasing of the rate of poverty, unemployment and imbalance of economy are the problem urgely to be handled. The competent human resources is a indicator of success of progressive country. A little of enterpreneur in a region, draws a low power to compete. To make a progress of good to compete, the joining teachers to be more active in giving motivation to be enterpeneur for their students. The scholars after graduating needed to be more inovative and creative in the matter of developing theirself, so that it can be relied on being created the job vacancy in order to the growing of economy in region will be developed and the rate of poverty will be decreased.